Analisis Peran Media Dalam Mengawasi Kasus Pelanggaran Terhadap Hak Pada Manusia Di Negara Indonesia - Faturohman Faturohman; Hasbari Hasbari; Adikusniyadi Adikusniyadi (Pusat Riset dan Inovasi Nasional, 2024)
Mass media has a very important function in creating public awareness, influencing opinion, and can also facilitate constructive dialogue regarding issues regarding human rights. In Indonesia, the mass media has a role as an independent watchdog that can help to reveal violations of rights, and can also inform the authorities to take appropriate action. Mass media is a means of communication used to disseminate information and other messages to a wide audience. Mass media covers various platforms and formats, including newspapers, magazines, radio, and so on. The main role of the mass media is to convey information to the public, who can monitor the actions of the government or related institutions. Mass media has the ability to reach large and geographically diverse audiences. With technological developments, mass media can now also offer interactivity, allowing audiences to participate in discussions, provide feedback, and even create their own content. Mass media plays a crucial role in forming a more open, informed, and critical society.